INTEREST ANALYSIS OF USING FINTECH OVO WITH TAM MODEL ON MSMEs IN DENPASAR CITY - Amor Waning, Diah Rachmafalen; Estiyanti, Ni Made; Putri, I Gst. Agung Pramesti Dwi (LPPM Universitas Nusa Mandiri, 2022)
The development of technology has now been felt in almost various sectors, one of which is the financial sector. Financial Technology (Fintech) is an innovation in the financial sector that can accelerate the process of financial services, one of which is digital payments. OVO is a type of digital payment with the widest acceptance in Indonesia because it has several partnerships, one of which is with MSMEs. Even so, the use of digital payments is still not massive among MSMEs. The reasons are, among others, the unsupported infrastructure and the perceived usefulness of the digital payment. This study aims to determine the factors that can affect the use of technology using a modified Technology Acceptance Model (TAM) by adding 2 external variables (system quality and culture). The method used is a quantitative method. The research data used primary data obtained directly from the respondents by distributing questionnaires. The data in this study will be analyzed using the PLS-based SEM method using the SmartPLS statistical tool. The results of this study show that as many as seven hypotheses can have a positive and significant effect on interest in using Fintech OVO, while there is one hypothesis that has a positive but not significant effect on interest in using Fintech OVO, namely the effect of perceived easy of use on perceived usefulness.